1999
DOI: 10.1046/j.1365-8711.1999.02262.x
|View full text |Cite
|
Sign up to set email alerts
|

  Pictoris: the variable Ca II H & K absorptions from 1994 to 1996

Abstract: We present high‐resolution spectroscopy of the variable Ca II H & K absorptions in the star β Pictoris. 313 spectra were obtained on 53 nights between 1994 November and 1996 December in order to characterize the behaviour of the lines and to test the falling evaporating bodies (FEB) scenario. Near‐continuous absorption activity was seen, including blueshifted features, one of which rivalled the strength of that reported in 1997 June by Crawford, Beust & Lagrange. Redshifted features at ∼ 5‐‐20 km s‐1 were pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 18 publications
2
30
0
Order By: Relevance
“…Freistetter et al 2007). The main indirect indicators are (i) the inner warped component of the β Pic circumstellar disk, together with additional asymmetries observed in the outer part (Mouillet et al 1997;Kalas & Jewitt 1995); (ii) the photometric transit-like event observed in 1981 (Lecavelier des Etangs et al 1997); and (iii) the cometary activity observed in the absorption spectrum of β Pic (Ferlet et al 1987;Lagrange et al 1996;VidalMadjar et al 1998;Petterson & Tobin 1999). We discuss below how each of these observational findings may be related to both the existence and the orbital and physical properties of β Pic b.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Freistetter et al 2007). The main indirect indicators are (i) the inner warped component of the β Pic circumstellar disk, together with additional asymmetries observed in the outer part (Mouillet et al 1997;Kalas & Jewitt 1995); (ii) the photometric transit-like event observed in 1981 (Lecavelier des Etangs et al 1997); and (iii) the cometary activity observed in the absorption spectrum of β Pic (Ferlet et al 1987;Lagrange et al 1996;VidalMadjar et al 1998;Petterson & Tobin 1999). We discuss below how each of these observational findings may be related to both the existence and the orbital and physical properties of β Pic b.…”
Section: Discussionmentioning
confidence: 99%
“…Transient redshifted spectral events have been regularly monitored in the absorption spectrum of β Pic (Ferlet et al 1987;Lagrange et al 1996;Vidal-Madjar et al 1998;Petterson & Tobin 1999), and attributed to the sublimation of numerous stargrazing planetesimals crossing the line of sight, which are referred to the falling evaporating bodies (FEBs) phenomenon. Their origin has been tentatively related to mean-motion resonances with a Jovian planet orbiting the star (Beust & Morbidelli 1996Thébault & Beust 2001;Beust & Valiron 2007).…”
Section: The β Pic Cometary Activitymentioning
confidence: 99%
“…In addition to these radio observations, optical surveys have revealed gas in the the debris disk systems HR 10 (Lagrange- Henri et al 1990), HD 32297 (Redfield 2007), 49 Ceti and ι Cyg (Montgomery & Welsh 2012), HD 2160, HD 110411, HD 145964, HD 183324 (Welsh & Montgomery 2013), and HD 17255 (Kiefer et al 2014). β Pic has been extensively studied using FUV/ optical gas tracers (e.g., Petterson & Tobin 1999;Roberge et al 2000Roberge et al , 2006Brandeker et al 2004) revealing a variable gas component due to the evaporation of comet-like bodies as they approach the central star. Far-infrared gas emission lines have also been detected by Herschel around HD172555 (Riviere-Marichalar et al 2012) and HD 32297 (Donaldson et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Aside from the expectation of acceleration given the likely orbits, hints that it should be detectable can be seen in previous works; Ferlet et al (1987) show a series of spectra taken over several hours, in which a redshifted line clearly accelerates by about 5 km s −1 , and temporal variation was also seen by Lagrange et al (1996) and Petterson & Tobin (1999) With the detection of such an acceleration, the distance derived from is thought to originate in a stable circumstellar disc, while the varying components are attributed to exocomet comae. Features at both low and high velocity are seen, with those at low velocity tending to be deeper.…”
Section: Motivationmentioning
confidence: 55%
“…the optical depth can be estimated from the line ratios, e.g. Lagrange-Henri et al 1992;Petterson & Tobin 1999).…”
Section: Detection Of Exocomet Accelerationmentioning
confidence: 99%